2007
DOI: 10.1007/s11172-007-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of electron-nuclear dynamics in 59Co NQR spectra of a series of cobaltocenium derivatives

Abstract: A coupling equation relating the quadrupole coupling constant (e 2 Qq zz ) to the asymmetry parameter (η) of the electric field gradient for a series of cobaltocenium derivatives ( 59 Co NQR) is derived. The estimates of the correlation times of "slow" modulations of electron motions by tunneling processes lie in the range from 10 -12 to 10 -14 s. This corresponds to the interval of the characteristic times of nuclear motions.The formation of a chemical bond between a metal atom and cyclopentadienyl rings in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…From these spectra, both peaks were simulated simultaneously using the QUEST software to obtain highly precise C Q ( 59 Co) and η Q values, which are reported in Table . The C Q ( 59 Co) values in this series of Co I catalysts are similar in magnitude to the values previously reported for Co I ‘sandwich’ compounds, Co(C 2 B 9 H 11 ) 2 − and Co(C 5 H 5 ) 2 + , as well as for cobaltocenium derivatives, which, taken together, suggests that the C Q ( 59 Co) values for Co I compounds tend to be larger than those for Co III compounds…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…From these spectra, both peaks were simulated simultaneously using the QUEST software to obtain highly precise C Q ( 59 Co) and η Q values, which are reported in Table . The C Q ( 59 Co) values in this series of Co I catalysts are similar in magnitude to the values previously reported for Co I ‘sandwich’ compounds, Co(C 2 B 9 H 11 ) 2 − and Co(C 5 H 5 ) 2 + , as well as for cobaltocenium derivatives, which, taken together, suggests that the C Q ( 59 Co) values for Co I compounds tend to be larger than those for Co III compounds…”
Section: Resultssupporting
confidence: 88%
“…From these spectra,b oth peaks were simulated simultaneously using the QUEST software [27] to obtain highly precise C Q ( 59 Co) and h Q values, which are reported in Table 3. The C Q ( 59 Co) valuesi nt his series of Co I catalysts are similari nm agnitude to the values previously reported for Co I 'sandwich' compounds, Co(C 2 B 9 H 11 ) 2 À and Co(C 5 H 5 ) 2 + , [19] as well as for cobaltocenium derivatives, [28,29] which, taken together,s uggests that the C Q ( 59 Co) valuesf or Co I compounds tend to be largerthan those for Co III compounds. [14] Since previous studies have reported ad ependence of the 59 Co EFG tensorp arameters on the experimental temperature, [30] we explored, using NQR spectroscopy,t he temperature sensitivity of the C Q ( 59 Co) and h Q values in compound 1.W hile varying the temperature between À10 8Ca nd + 40 8C, the high frequencyN QR peak remained unchanged, whereas the low frequencyp eak shifted to as lightly lower frequency by % 140 kHzo ver the temperature range.…”
Section: Co Nqr Experimentsmentioning
confidence: 99%